2021
DOI: 10.1002/ijc.33757
|View full text |Cite
|
Sign up to set email alerts
|

Association between body mass index and colorectal adenomas: Findings from a case‐control study in Vietnam

Abstract: Colorectal cancer is a leading cancer worldwide and in Vietnam. Adenomas (adenomatous polyps) is an important precursor of colorectal cancer. There is currently no study to determine the modifiable risk factors for colorectal adenomas, including body mass index (BMI) in Vietnam. We conducted an individually matched case-control study of 1149 colorectal adenomas and 1145 controls in a large-scale colorectal screening program involving 103 542 individuals aged 40-75 years old in Hanoi, Vietnam. Conditional logis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…Among them, several studies have found the significant positive association of general obesity with the risk of ADs in different populations, [25][26][27][28] nevertheless, other studies showed this positive association but did not achieve statistical significance. 29,30 The findings were similar for its association with the risk of SPs. [31][32][33] Moreover, there are also studies investigating these two lesions simultaneously.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…Among them, several studies have found the significant positive association of general obesity with the risk of ADs in different populations, [25][26][27][28] nevertheless, other studies showed this positive association but did not achieve statistical significance. 29,30 The findings were similar for its association with the risk of SPs. [31][32][33] Moreover, there are also studies investigating these two lesions simultaneously.…”
Section: Discussionsupporting
confidence: 59%
“…Over the past two decades, the association of general obesity with the risk of colorectal precancerous lesions was largely performed in single type. Among them, several studies have found the significant positive association of general obesity with the risk of ADs in different populations, 25‐28 nevertheless, other studies showed this positive association but did not achieve statistical significance 29,30 . The findings were similar for its association with the risk of SPs 31‐33 .…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Further, a more recent study in 2021 has declared the reciprocal relation between BMI and the incidence rate of colorectal polyps. Namely, authors have claimed that thinner patients with lower BMI values manifested a higher explosion rate of colorectal polyps, although no data about histopathological changes was explained 25 .…”
Section: Discussionmentioning
confidence: 99%